P289 Evaluation of the safety and effectiveness of direct-acting antiviral drugs in the treatment of hepatitis C in patients with inflammatory bowel disease: National multicenter study (ENEIDA registry). MIC project. (21st January 2022) - Martin Cardona, A; Horta, D; Florez-Diez, P; Vela, M; Mesonero, F; Ramos Belinchón, C; García, M J; Masnou, H; de la Peña-Negro, L; Suárez Ferrer, C; Casanova, M J; Ortiz Durán, M; et al.
Abstract: Background: The prevalence of hepatitis C virus infection (HCV) in patients with inflammatory bowel disease (IBD) ranges from 1–6%. Direct-acting antivirals (DAAs), with cure rates >90%, represent a radical change from interferon-based therapies. The ECCO guidelines (Kucharzik JCC 2021) warns about the risk of IBD reactivation due to the effect of DAAs, but HCV management in this situation is uncertain given the lack of evidence. AIMS: To evaluate: 1) Effectiveness and safety of DAAs in IBD; 2) Interaction of DAAs with IBD drugs, particularly immunosuppressants and/or biologics. Methods: Multicenter retrospective study of patients with IBD and HCV treated with DAAs identified on the ENEIDA registry (January 2011-February 2021). Variables evaluated: age, gender, location, extent, phenotype and activity of IBD, treatments, anti-HCV and viral load, DAA treatment and duration, fibrosis and hepatic decompensations, adverse effects (AE) and interactions. Results: We included 79 patients with IBD and HCV treated with DAAs (47 sofosbuvir, 28 ledipasvir, 7 daclatasvir, 8 velpatasvir, 1 simeprevir, 16 paritaprevir+ritonavir+ombitasvir, 14 dasabuvir, 3 grazoprevir+elbasvir, 13 glecaprevir+pibrentasvir). Clinical and demographic characteristics: mean age (years) 54+/-12.66SD; 62% male, 77.2% genotype 1, 32.6% advanced fibrosis (none Child B-C). A 78.5% (n=62) received IBD treatment (39 salicylates, 20 azathioprine, 1 methotrexate, 4 corticosteroids, 10 antiTNF, 2 vedolizumab, 2 ustekinumab, 1 apheresis). A 17.7% (n=14) had active IBD (64.3% remained unchanged, 21.4% improved and 14.3% worsened) and 82.3% (n=65) were inactive at the onset of ADD. Of these, 9.2% (n=6) developed mild-moderate activity (4 mild and 2 moderate). In 85% (n=67) no treatment changes were made, in 9% (n=7) it was intensified and in 6% (n=5) it was de-intensified. Adherence to DAAs and sustained virologic response was obtained in 96.2% (n=76). A total of 7 (8.9%) AE were notified, of which 5 were possibly/probably related to DAAs (100% mild) and 2 were unrelated (1 azathioprine withdrawal due to pancytopenia). The AE were unrelated with the presence of inflammatory activity, type of IBD, liver fibrosis, use of immunosuppressants, biologics, or with any DAA regimen. Conclusion: This is the first reported series of IBD patients infected with HCV and treated with DAAs, we showed that DAA are effective and safe. They do not trigger IBD flare-ups, nor have more AE than in patients without IBD. Moreover, they do not have clinically significant pharmacological interactions with immunosuppressants and/or biologics. Thus, the eradication of HCV with DAA in IBD patients must be the same of the HCV infected patients without IBD, based on EASL recommendations.